Nonlinear Coupling between Cortical Oscillations and Muscle Activity during Isotonic Wrist Flexion - Yang, Yuan; Solis-Escalante, Teodoro; van de Ruit, Mark; van der Helm, Frans C. T.; Schouten, Alfred C. (Frontiers in Computational Neuroscience, 2016)
Coupling between cortical oscillations and muscle activity facilitates neuronal communication during motor control. The linear part of this coupling, known as corticomuscular coherence, has received substantial attention, even though neuronal communication underlying motor control has been demonstrated to be highly nonlinear. A full assessment of corticomuscular coupling, including the nonlinear part, is essential to understand the neuronal communication within the sensorimotor system. In this study, we applied the recently developed n:m coherence method to assess nonlinear corticomuscular coupling during isotonic wrist flexion. The n:m coherence is a generalized metric for quantifying nonlinear cross-frequency coupling as well as linear iso-frequency coupling. By using independent component analysis and equivalent current dipole source localization, we identify four sensorimotor related brain areas based on the locations of the dipoles, i.e. the contralateral primary sensorimotor areas, supplementary motor area, prefrontal area and posterior parietal cortex. For all these areas, linear coupling between EEG and EMG is present with peaks in the beta band (15-35 Hz), while nonlinear coupling is detected with both integer (1:2, 1:3, 1:4) and non-integer (2:3) harmonics. Significant differences between brain areas is shown in linear coupling with stronger coherence for the primary sensorimotor areas and motor association cortices (supplementary motor area, prefrontal area) compared to the sensory association area (posterior parietal cortex); but not for the nonlinear coupling. Moreover, the detected nonlinear coupling is similar to previously reported nonlinear coupling of cortical activity to somatosensory stimuli. We suggest that the descending motor pathways mainly contribute to linear corticomuscular coupling, while nonlinear coupling likely originates from sensory feedback.